Efficacy and safety of hyaluronic acid fillers for lip augmentation in a Chinese population. (7th February 2022) - Guo, Yanping; Wei, Wuhan; Li, Qiang; Tao, Changbo; Li, Xueyang; Zhang, Aijun; Jin, Peisheng
Abstract: Background: Hyaluronic acid (HA) is an effective dermal filler for facial rejuvenation. This study aimed to observe the clinical efficacy of HA injection for lip augmentation in Chinese patients. Methods: From May 2019 to April 2020, 70 patients with lip fullness scale (LPS) ≤3 underwent local HA injection using the "three‐point" injection technique. All patients were followed up to observe the clinical efficacy, LPS, adverse events, and complications. Results: All 70 patients were followed up for 12 months. Statistically significant improvements were observed in the height of lips within 6–9 months post‐treatment ( p < 0.05). The LFS improved significantly at follow‐up compared with baseline ( p < 0.05). Local redness occurred in two patients, and serious swelling occurred in three patients. These adverse events were generally tolerated and disappeared gradually within 1 week. No other serious adverse events and complications were reported in the remaining patients. Conclusions: Hyaluronic acid injection can be used for lip augmentation in the Chinese population. The "three‐point" technique is simple, safe, and effective and does not cause serious complications.